MicroRNAs in Taenia solium Neurocysticercosis: Insights as Promising Agents in Host-Parasite Interaction and Their Potential as Biomarkers - Gutierrez-Loli, Renzo; Orrego, Miguel A.; Sevillano-Quispe, Oscar G.; Herrera-Arrasco, Luis; Guerra-Giraldez, Cristina (Frontiers in Microbiology, 2017)
MicroRNAs (miRNAs) are short, endogenous, non-coding, single-stranded RNAs involved in post-transcriptional gene regulation. Although several miRNAs have been identified in parasitic helminths, there is little information about their identification and function in Taenia. Furthermore, the impact of miRNAs in neurocysticercosis, the brain infection caused by larvae of Taenia solium is still unknown. During chronic infection, T. solium may activate numerous mechanisms aimed to modulate host immune responses. Helminthic miRNAs might also have effects on host mRNA expression and thus play an important role regulating host-parasite interactions. Also, the diagnosis of this disease is difficult and it usually requires neuroimaging and confirmatory serology. Since miRNAs are stable when released, they can be detected in body fluids and therefore have potential to diagnose infection, determine parasite burden and ascertain the effectiveness of treatment or disease progression, for instance. This review discusses the potential roles of miRNAs in T. solium infection, including regulation of host-parasite relationships and their eventual use as diagnostic or disease biomarkers. Additionally, we summarize the bioinformatics resources available for identification of T. solium miRNAs and prediction of their targets.